2002
DOI: 10.1002/ijc.10650
|View full text |Cite
|
Sign up to set email alerts
|

Gene therapy for intraperitoneally disseminated pancreatic cancers by Escherichia coli uracil phosphoribosiltransferase (UPRT) gene mediated by restricted replication‐competent adenoviral vectors

Abstract: Although patients with unresectable pancreatic tumors have been treated with 5-fluorouracil (5FU)-based combination chemotherapy, the drug resistance of cancer cells presents a crucial therapeutic problem. It was reported that UPRT overcomes 5FU resistance. UPRT catalyzes the synthesis of 5-fluorouridine monophosphate (FUMP) from Uracil and phosphoribosylpyrophosphate (PRPP). The antitumor effect of 5FU is enhanced by augmenting 5-fluorodeoxyuridine monophosphate (FdUMP) converted from FUMP, which inhibits thy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…As we previously described, the E1B mutant virus did replicate in pancreatic cancer cells in vitro and inhibited the tumor growth in vivo. 28,49,50 These data strongly suggested that the oncolytic replication-competent Adv is a promising tool for gene therapy against pancreatic cancer.…”
Section: Discussionmentioning
confidence: 92%
“…As we previously described, the E1B mutant virus did replicate in pancreatic cancer cells in vitro and inhibited the tumor growth in vivo. 28,49,50 These data strongly suggested that the oncolytic replication-competent Adv is a promising tool for gene therapy against pancreatic cancer.…”
Section: Discussionmentioning
confidence: 92%
“…The feasibility and safety of CRAds in human patients have been demonstrated in many clinical trials (Aghi and Martuza, 2005). However, the promising results obtained with early-generation CRAds in animal models of liver and pancreatic cancer (Oonuma et al, 2002;Takahashi et al, 2002) have not been reproduced in humans, at least as single agents (Habib et al, 2002;Hecht et al, 2003;Makower et al, 2003). Improved versions of CRAds are being generated, but the preclinical evaluation of these viruses is still hampered by the fact that human adenovirus does not replicate efficiently in mice and rats.…”
Section: Introductionmentioning
confidence: 95%
“…In vivo gene transduction of UPRT, using a replication-incompetent adenovirus, resulted in the regression of intraperitoneal pancreatic tumours, although the high doses of adenovirus required to obtain a complete response produced severe dehydration and diarrhoea as adverse effects. 42 A replication-selective adenovirus expressing UPRT, AxE1 AdB-UPRT, was subsequently developed and evaluated in a disseminated intraperitoneal pancreatic cancer model. Combined treatment with 5-FU and the adenoviral agent dramatically reduced the tumour burden without adverse effects 42 and this may be a useful approach in overcoming drug resistance.…”
Section: Delivery Of Cytokines With Axe1adbmentioning
confidence: 99%
“…42 A replication-selective adenovirus expressing UPRT, AxE1 AdB-UPRT, was subsequently developed and evaluated in a disseminated intraperitoneal pancreatic cancer model. Combined treatment with 5-FU and the adenoviral agent dramatically reduced the tumour burden without adverse effects 42 and this may be a useful approach in overcoming drug resistance.…”
Section: Delivery Of Cytokines With Axe1adbmentioning
confidence: 99%